MEDIA PEMBELAJARAN SEBAGAI SARANA KOMUNIKASI MATEMATIKA DI SEKOLAH DASAR - Rivdya Eliza (Ta'dib, 2010)
Rapid developments in information technology and communication today is based on the development of mathematics in the field of number theory, algebra, analysis, theory of chances and discrete mathematics. To master the technology and creating future required a strong mastery of mathematics from an early age. Standard mathematical competence and basic competence in elementary school (SD), Junior Secondary School (SMP) and High School (SMA) have been prepared with the intention to develop the ability to use mathematics in solving problems and communicating the idea or the idea of using symbols, tables, diagrams , and other media. At the elementary school where children are in the concrete operational stage and how to effectively communicate the idea of mathematical ideas is to use instructional media. This paper will try to review the instructional media as one means of communication of mathematics learning in elementary school (SD).Kata kunci: komunikasi, media pembelajaran